(untitled) (Carte Romanze, 2014)
Le roman de Cleomadès d’Adenet le Roi a donné lieu au XVe siècle à deux mises en prose, dont seule la plus courte est passée sous les presses, tant françaises qu’espagnoles. L’examen des imprimés lyonnais veut montrer que, parallèlement aux productions troyennes et parisiennes, un Clamadès spécifiquement lyonnais semble se dessiner, depuis l’editio princeps de Guillaume Le Roy, pour atteindre son aboutissement au début du XVIe siècle. En revanche, le dernier imprimé lyonnais rompt le rapport de succession linéaire et laisse entendre que nous ne disposons aujourd’hui que de quelques témoins d’une tradition bien plus complexe. The romance of Cleomadès by Adenet le Roi was translated into prose twice in the 15th century, but only the shorter, known as Clamadès, was printed in France as well as in Spain. The review of the editions of Clamadès printed in Lyon tends to show that, beside the other French productions, the editio princeps by Guillaume Le Roy has given rise to an independent tradition that culminates in the early 16th century. By way of contrast, the last edition of Clamadès printed in Lyon breaks the straight-line relationship between the different witnesses and implies that we only have a few tracks and trails left from a much more complex tradition.